2005
DOI: 10.1097/01.pep.0000163073.50852.58
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Early Physical Therapy Intervention for Very Preterm, Very Low Birth Weight Infants: A Randomized Controlled Clinical Trial

Abstract: PT intervention does not significantly affect motor performance of infants born very preterm with VLBW at four months CA. Parental compliance and intervention frequency may have influenced the outcome. Preliminary evidence suggests that neonatal and early PT may reduce the incidence of motor delay among infants born very preterm with VLBW. Follow-up of this group is recommended to ascertain the long-term benefits of this type of early PT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 67 publications
3
99
1
5
Order By: Relevance
“…However, compliance was defined as remembering activities included in the intervention and not actual time spent on the intervention. 32 In our study, we found no association between total time spent on the intervention and infant motor performance. Although the total number of sessions was less than intended, a significant difference was found in change in motor performance between the intervention and control groups between 34 and 37 weeks' PMA.…”
Section: Figurecontrasting
confidence: 69%
See 1 more Smart Citation
“…However, compliance was defined as remembering activities included in the intervention and not actual time spent on the intervention. 32 In our study, we found no association between total time spent on the intervention and infant motor performance. Although the total number of sessions was less than intended, a significant difference was found in change in motor performance between the intervention and control groups between 34 and 37 weeks' PMA.…”
Section: Figurecontrasting
confidence: 69%
“…The median duration of each session was 9 minutes, close to the maximum intended duration. This dosage is similar to the intended dosage in another study of early PT by Cameron et al, 32 included in the review of Spittle et al 14 Not many studies of early PT have included reports on compliance. In the aforementioned study, infants of parents with good compliance had higher percentile ranks on the Alberta Infant Motor Scale at 4 months compared with those with moderate or poor compliance (median 75th versus 46th percentile; P = .05).…”
Section: Figurementioning
confidence: 91%
“…In our study, EI therapy helps in the process of achieving higher level of achievement in gross motor domain, similar studies 37,38,39 is in agreement with our result.…”
Section: Discussionsupporting
confidence: 82%
“…1. There were 18 RCTs or quasi-RCTs of early developmental interventions after hospital discharge [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] involving 2686 infants (Table I). Eleven of these had data suitable for use in metaanalysis (Tables SII and SIII).…”
Section: Resultsmentioning
confidence: 99%
“…This makes it difficult to distinguish whether there is an effect on motor outcome and, if not, whether the measures are sensitive enough to detect the effects of intervention. Specific motor assessments, such as the Alberta Infant Motor Scale, the TIMP, and the Movement Assessment Battery for Children were used only by individual studies, 26,28,38 and these data could not be pooled for meta-analysis. Lekskulchai and Cole 28 demonstrated a significant effect of intervention using the TIMP with short-term (4mo corrected age) follow-up.…”
Section: Discussionmentioning
confidence: 99%